Nitrogen-protected thermal induction combined with Microbial Transglutaminase (MTG) cross-linking enhances functional properties and gel structure of Soy Protein Isolate relevant to gel-based feed formulation - Yong Guo; Ling Qu (PLoS ONE, 2026)
Protein-based gel matrices are increasingly explored for feed applications requiring soft or semi-solid formulations, but achieving strong gelation along with high water- and oil-holding capacities at low protein concentrations remains challenging. In this study, soy protein isolate (SPI) was modified via nitrogen-protected thermal induction followed by microbial transglutaminase (MTG) cross-linking to enhance its suitability as a gel-feed matrix. Single-factor and orthogonal experimental designs were used to investigate the effects of SPI concentration, MTG dosage, reaction temperature, reaction time, and pH on macroscopic gelation (measured as apparent viscosity), nitrogen solubility index (NSI), water-holding capacity (WHC), oil-holding capacity (OHC), and microstructure (SEM). Under optimized conditions—10% SPI, 0.3% MTG, 50 °C, 3 h, pH 7—gelation increased by approximately 373%, WHC improved by 222%, and OHC increased by 150%, while SEM confirmed the formation of a more regular three-dimensional network compared with native SPI. These results indicate that dual-modified SPI exhibits enhanced functional properties relevant to gel-feed formulations, providing a practical foundation for laboratory-scale process optimization. Further pilot-scale evaluation and biological validation are warranted to assess scalability, processing efficiency, and performance in target animal applications.